2021
DOI: 10.1002/jev2.12135
|View full text |Cite
|
Sign up to set email alerts
|

TPI1‐reduced extracellular vesicles mediated by Rab20 downregulation promotes aerobic glycolysis to drive hepatocarcinogenesis

Abstract: Rab GTPases are major mediators that ensure the proper spatiotemporal regulation of intracellular trafficking. Functional impairment and altered expression of Rab proteins have been revealed in various human cancers. There is an emerging evidence about the role of Rab proteins in the biogenesis of extracellular vesicles (EVs). In hepatocellular carcinoma (HCC), using RNA sequencing comparing expression profiles of adjacent non‐tumorous tissues and HCC, Rab20 is identified to be the most frequently downregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…Recent studies have revealed that RAB20, which plays a role in the control of endocytotic vesicle transport, is involved in the progression of multiple cancers [ 15 , 16 , 17 , 36 ]. Amillet et al [ 15 ] first identified that the overexpression of RAB20 in pancreatic intraductal neoplasia lesions is an early event in the course of pancreatic cancer progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that RAB20, which plays a role in the control of endocytotic vesicle transport, is involved in the progression of multiple cancers [ 15 , 16 , 17 , 36 ]. Amillet et al [ 15 ] first identified that the overexpression of RAB20 in pancreatic intraductal neoplasia lesions is an early event in the course of pancreatic cancer progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on neuronal network formation showed that RAB20, as a novel regulator, participated in neurite outgrowth and cell proliferation [ 37 ]. Liu et al [ 36 ] found that the restoration of RAB20 expression in hepatocellular carcinoma cells inhibited cell growth, motility, and metastasis. To further investigate the oncogenic functions of RAB20 in regulating the malignant phenotype, validation and rescue experiments were conducted in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TPI1 and RAN exerted crucial effects on tumor initiation and progression [ 37 40 ]. For example, the reduction of TPI1 in extracellular vesicles mediated by Rab20 downregulation facilitates aerobic glycolysis to drive hepatocarcinogenesis [ 41 ]. RAN promotes membrane targeting and stabilization of RhoA to enhance ovarian cancer cell growth and invasiveness [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…RAB20 expression was downregulated in proliferative SMCs (P-value <0.001). Downregulation of RAB20 has been shown to promote glycolysis and contribute to enhanced cell proliferation and motility 48 . KD analysis identified a novel KD gene in the proliferative BN, MPI.…”
Section: Metabolic Pathway Enrichment In Unpreserved Modulesmentioning
confidence: 99%